2000
DOI: 10.5144/0256-4947.2000.129
|View full text |Cite
|
Sign up to set email alerts
|

Threshold Stage of Retinopathy of Prematurity: Maternal and Neonatal Risk Factors

Abstract: Background:The aim of this study was to review the maternal and neonatal risk factors associated with retinopathy of prematurity (ROP) and the threshold stage of the disease. Patients and Methods: In this prospective cohort study, all preterm infants of less than 1501 g birth weight were screened for ROP between January 1996 and December 1997 at the neonatal unit of the Maternity Hospital in Kuwait. The rate of the threshold stage of ROP, as well as risk factors associated with the disease, were identified. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
(20 reference statements)
0
16
0
1
Order By: Relevance
“…Other risk factors found to be significant were the presence of sepsis, NEC, number of ventilated days, number of blood units transfused, need for medical or surgical treatment for PDA, and HMD of grade 3 or more [Tables 1 and 2]. Other studies too have found low BW, low GA, respiratory distress syndrome, number of blood units transfused, and number of ventilated days to be significant risk factors for the development of severe ROP requiring treatment among the screened population 7920–222426…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors found to be significant were the presence of sepsis, NEC, number of ventilated days, number of blood units transfused, need for medical or surgical treatment for PDA, and HMD of grade 3 or more [Tables 1 and 2]. Other studies too have found low BW, low GA, respiratory distress syndrome, number of blood units transfused, and number of ventilated days to be significant risk factors for the development of severe ROP requiring treatment among the screened population 7920–222426…”
Section: Discussionmentioning
confidence: 99%
“…[7121516] In a study conducted in our center in 1996-97, ROP was found among 64.5% of babies with birth weight of less than 2000 g.[17] The higher incidence of ROP could be due to smaller babies in the earlier cohort. [17] A decreasing incidence of ROP has been observed by some authors[4519] and this has been attributed to the introduction of use of Surfactant[5] or to the improving neonatal care and better monitoring of oxygen saturation. [19]…”
Section: Discussionmentioning
confidence: 99%
“…Low birth weight has been consistently found to be significant for the development of threshold disease in other studies too. [61217] Some studies have found presence of IVH[13] and fungal infection[14] to be significant for the development of threshold disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors beyond low gestational age (GA) at birth and low postnatal levels of IGF-I that have been identified as risk factors for ROP include low birth weight and poor postnatal growth, sub-optimal oxygen therapy, depletion of the maternal supply of growth and nutritional factors, and red blood cell transfusion [1,46]. In addition to risk factors specifically associated with preterm birth, perinatal or neonatal infections followed by a systemic inflammatory response with the activation of pro-inflammatory cytokines have been suggested to increase the risk for severe ROP [710], but contradictory data have been reported [1113]. …”
Section: Introductionmentioning
confidence: 99%